Konseling Individu dengan Pendekatan Eksistensial Humanistik dalam Meningkatkan Karakter Religius Siswa di Ponpes Al Khalifah - Mitahul Rahmah; Dina Hajja Ristianti; Sumarto Sumarto (ALSYS, 2025)
Islamic boarding schools (pondok pesantren) play a strategic role in shaping students' character and religious attitudes, which are reflected not only in adherence to religious rituals but also in the ability to internalize spiritual values in daily life. However, not all students are able to develop religious attitudes optimally. This study aims to explore the effectiveness of the existential-humanistic counseling approach in enhancing students' religious character at Pondok Pesantren Al Khalifah. A literature review method with a qualitative approach was used, involving guidance and counseling teachers and students as the primary subjects. The findings indicate that the existential-humanistic counseling approach—emphasizing empathetic counselor-student relationships, unconditional acceptance, and the enhancement of self-awareness—is effective in helping students understand personal responsibility and freedom in practicing religious teachings. This approach also encourages deep exploration of life’s meaning and spiritual values, fostering authentic and meaningful religious attitudes. Furthermore, it supports students in dealing with existential anxiety and facilitates the conscious internalization of Islamic teachings with a strong sense of accountability. In conclusion, existential-humanistic counseling significantly contributes to the development of strong, independent, and devout religious character within the pesantren educational context.